Current Advances and Future Prospects in Cancer Immunotherapeutics - Zeynep DEDE; Kader TUMER; Tugce KAN; Burcu YUCEL (Medeniyet Medical Journal)
Cancer is a disease that results from the uncontrolled proliferation and growth of cells. Due to early detection methods, there is a decrease in death rates in many types of cancer. However, among the causes of death worldwide, cancer still ranks second after cardiovascular diseases. Therefore, cancer research has focused mainly on developing more effective treatments to reduce deaths from cancer. With a better understanding of the molecular mechanisms in cancer cells, advances in cancer treatment have evolved and changed. The main priority of research is to develop treatment modalities with the highest response rate and less side effects. In this context, immunotherapies have started a new era in cancer treatments. In this review, an overview of the future of next-generation treatment methods is presented by including the most preferred immunotherapy methods.